Enhancing navigation and obstacle avoidance with a vibrotactile device as secondary electronic travel aid. - de Paz, Carlos; Huertas, Juan Antonio; Ibáñez-Gijón, Jorge; Martín-Gonzalo, Juan Andrés; Varas, Ana Belén; Travieso, David (Disability & Rehabilitation: Assistive Technology, 2025)
People with visual impairments commonly rely on the use of a white cane to navigate and avoid obstacles. Although this analog tool is highly reliable and easy to use, its drawback is the impossibility to anticipate obstacles beyond reach and routes, as well as obstacles above waist level. Electronic travel aids (ETAs) and sensory substitution devices (SSDs) are new technological solutions designed to enhance the tactile and/or auditory capabilities to access the information needed to overcome those drawbacks. In the present study, 25 individuals with visual impairments used the T-Sight, a vibrotactile SSD, and/or the white cane in a navigation task involving obstacle avoidance. While the performance achieved with the device, measured by the number of collisions and walking speed, did not surpass the white cane, the SSD did have a positive impact on ambulation. Participants reduced the number of white cane touches towards environmental obstacles and performed obstacle avoidance maneuvers earlier. These results demonstrate the potential of vibrotactile devices to address the limitations of the white cane. IMPLICATIONS FOR REHABILITATION: Assessments of secondary travel aids for people with visual impairments should include performance measures beyond speed and number of collisions. These include the number of alerts, white cane touches, and trajectory analysis. Our vibrotactile secondary ETA allows improvements in navigation and obstacle avoidance shown as a reduction in the use of the white cane and an anticipation of the avoidance maneuvers.